2014
DOI: 10.1007/s00345-014-1393-3
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic results, functional outcomes, and complication rates of robotic-assisted radical prostatectomy: multicenter experience in Turkey including 1,499 patients

Abstract: Our analyses including high-volume centers, which is the first largest series in Turkey, show that RARP is a safe procedure, has low PSM rates, high continence, and potency rates for the treatment of localized PC at experienced centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
2
7
0
1
Order By: Relevance
“…Our sexual function outcomes were similar to other nonselected RARP cohorts from high‐volume centres (Tasci et al, ; Tholomier et al, ); at 12 months post‐operatively, the overall mean sexual function score in nerve‐sparing patients was 45.0 ± 30.0, and the median score was 40.…”
Section: Discussionsupporting
confidence: 85%
“…Our sexual function outcomes were similar to other nonselected RARP cohorts from high‐volume centres (Tasci et al, ; Tholomier et al, ); at 12 months post‐operatively, the overall mean sexual function score in nerve‐sparing patients was 45.0 ± 30.0, and the median score was 40.…”
Section: Discussionsupporting
confidence: 85%
“…Wedmid et al [25] reported that the incidence of rectal injury during RARP is 0.17% based on a large number of 6,650 RARP cases in the USA. In the multicenter experience of 1,499 patients who underwent RARP by Tasci et al [26] , the incidence of rectal injury is 0.13%, which is similar to that in the current study (0.18%) where most procedures were performed by surgeons during their learning curve. Previous ORP [27][28][29][30] and standard LRP [31][32][33] series showed incidences of 0.5 and 0.7-2.0%, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…Besides oncological outcomes, RP might be associated with urinary incontinence and erectile dysfunction (ED), which both represent functional impairments in regard to postoperative quality of life [2,3]. According to recent guidelines and reports in the literature, extended pelvic lymph node dissection (ePLND) is recommended in intermediate-and high-risk PCa according to D'Amico [4,5].…”
Section: Introductionmentioning
confidence: 99%